2007
DOI: 10.1093/ndt/gfm111
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in health care providers of dialysis service in Northern Italy a multicentre study

Abstract: Although burnout is not a general problem in dialysis health care providers, a subgroup of them may be identified, who would benefit from supportive measures to prevent this condition. Nurses appeared more burned-out in the emotional exhaustion scale than physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
5
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 24 publications
7
64
5
9
Order By: Relevance
“…Psychosocial aspects refer to the interaction between work environment, content and conditions and worker capacity, needs, culture, extra-work personal elements, which may, according to perception and experience, influence health, satisfaction, and work performance [14][15][16].…”
Section: -Individual Factors -Environmental Factors -Economical Factorsmentioning
confidence: 99%
“…Psychosocial aspects refer to the interaction between work environment, content and conditions and worker capacity, needs, culture, extra-work personal elements, which may, according to perception and experience, influence health, satisfaction, and work performance [14][15][16].…”
Section: -Individual Factors -Environmental Factors -Economical Factorsmentioning
confidence: 99%
“…[30] Long-term emotional stress at work can increase the risk of emotional exhaustion. [31,32] Jones et al showed that haemodialysis staff often experienced an aggressive work environment related to patients' frustration and anger over waiting to be put on or taken off the dialysis machine, having to wait for transportation back and forth from the dialysis centre (sometimes for hours), and how the disease and treatment regime limits their quality of life (e.g. a restricted diet and fluid management, sexual dysfunction, and limited spare time and social life).…”
Section: Discussionmentioning
confidence: 99%
“…Klersy i wsp. [31] przebadali personel medyczny (lekarze i pielęgniarki) pracujący na oddziałach dializoterapii w szpitalach północnych Włoch. U 30% pielęgniarek i 18% lekarzy wykazano wysoki poziom BS, co autorzy uważają za wynik niższy od spodziewanego, jako że, według powyższych autorów, przegląd piśmiennictwa wskazuje średnio na 25-30-procentowy poziom BS wśród personelu medycznego.…”
Section: Dyskusjaunclassified
“…W badaniu Klersy i wsp. [31] pielęgniar-ki (grupa zawodowa zdecydowanie zdominowana przez kobiety) osiągnęły większe wartości w skali wyczerpania emocjonalnego niż lekarze (brak zdecydowanej dominacji jednej z płci). Wielu autorów zwraca uwagę na fakt, że kobiety wykazują tendencję do większych wartości punktacji w skali wyczerpania emocjonalnego niż mężczyźni [32][33][34][35].…”
Section: Dyskusjaunclassified